Research on the construction of corneal endothelium transplantation with acellular amniotic membrane as a scaffold - Chen, Ya-Nan; Guo, Rui-Qin; Liang, Bo-Yu; Ke, Hong-Qin; Dong, Meng-Jie; He, Ming-Fang; Yang, Ji; Liu, Hai (Frontiers in Medicine, 2025)
IntroductionThis study aimed to develop a human acellular amniotic membrane (HAAM) scaffold suitable for corneal endothelial transplantation. The HAAM was engineered using sequential chemical treatments and physical agitation to remove cellular components while preserving the extracellular matrix structure. The study sought to evaluate the biocompatibility and functional properties of the HAAM when seeded with immortalized human corneal endothelial cells (HCECs), with the ultimate goal of providing a potential therapeutic option for corneal endothelial dysfunction.MethodsThe HAAM was fabricated through a series of chemical treatments involving trypsin/EDTA, Triton X-100, sodium deoxycholate, and peracetic acid/ethanol, combined with physical agitation. Following lyophilization, the HAAM was sterilized and coated with fibronectin and chondroitin sulfate (FNC) to enhance cell adhesion. HCECs were then seeded onto the HAAM scaffold. Biocompatibility was assessed by evaluating cell adhesion using microscopy, cell viability using CCK-8 and EdU assays, and cell proliferation. Functional validation included immunofluorescence detection of tight junction proteins (ZO-1), transcriptome sequencing (RNA-seq), and quantitative PCR (qPCR) to analyze the expression of genes regulating barrier function, ion transport, and extracellular matrix synthesis. Additionally, the expression of key genes critical for endothelial function was assessed to validate the functionality of the HAAM-based corneal endothelial transplantation membrane.ResultsThe HAAM was successfully prepared, maintaining an intact collagen fiber structure. HCECs adhered closely to the HAAM scaffold, forming a continuous monolayer. The HAAM promoted cell viability and proliferation, as evidenced by positive expression of tight junction proteins and upregulation of key functional genes. Transcriptome analysis identified genes involved in proliferation and matrix synthesis, further supporting the biocompatibility and functional properties of the HAAM.DiscussionThe HAAM scaffold demonstrated excellent transparency, mechanical properties, and biocompatibility, making it suitable for the attachment and proliferation of HCECs. The effective maintenance of key functional gene expression levels suggests that the HAAM functionally mimics the characteristics of the natural corneal endothelial layer. These findings provide experimental evidence for the potential clinical application of the HAAM in corneal endothelial transplantation, offering a promising therapeutic option for patients with corneal endothelial dysfunction. Further studies are warranted to explore the long-term efficacy and safety of the HAAM in preclinical and clinical settings.